Answer:
<em>(1, 7) </em>
Step-by-step explanation:
y = 3x + 4
y = 6x + 1
6x + 1 = 3x + 4 ⇒ x = 1
y = 3(1) + 4 = 7
<em>(1, 7)</em>
Answer:
steps below
Step-by-step explanation:
f(x) = x + 5
g(x) = x - 4
f(g(x)) = f(x-4) = (x-4) + 5
Answer:
x = 5
Step-by-step explanation:
Using the fact that line segments AB and BC are parts of the whole line segment AC, we can write the following equation:
AB + BC = AC
Now, using the given values, we can substitute in for the equation and solve for x:
AB + BC = AC
9 + 2x - 5 = x + 9
2x + 4 = x + 9
x = 5
Thus, we have found that for these sets of equations for these line segments, our value for x should be 5.
Cheers.
Hence the value of the expression above are as listed below
<em>f(6+4) = 25</em>
<em>f(6)+f(4) = 20</em>
<em>f(6-4) = 1</em>
<em>f(6)-f(4) = 6</em>
<em>f(6*4) = 67</em>
<em>f(6)*f(4) = 91</em>
<h3>Functions and values</h3>
Given the expression below f(x) = 3x - 5
f(6+4) = f(10) =3(10) - 5
f(6+4) = 25
f(6) = 3(6) - 5
f(6) = 18 - 5 = 13
f(4) = 3(4) - 5
f(4) = 7
f(6)+f(4) = 13+7
f(6)+f(4) = 20
f(6-4) = f(2) =3(2) - 5
f(6-4) = 1
f(6) = 3(6) - 5
f(6) = 18 - 5 = 13
f(4) = 3(4) - 5
f(4) = 7
f(6)-f(4) = 13-7
f(6)-f(4) = 6
f(6*4) = f(24) =3(24) - 5
f(6*4) = 67
f(6) = 3(6) - 5
f(6) = 18 - 5 = 13
f(4) = 3(4) - 5
f(4) = 7
f(6)*f(4) = 13*7
f(6)*f(4) = 91
Learn more on function and values here: brainly.com/question/2284360
#SPJ1